Conduction Mechanisms and Environmental Sensitivity of Solution-Processed Silicon Nanoparticle Layers for Thin-Film Transistors - Weis, Sebastian; Körmer, Richard; Jank, Michael; Lemberger, Martin; Otto, Michael; Ryssel, Heiner; Peukert, Wolfgang; Frey, Lothar (Small, 2011)
Room-temperature, solution-processed, silicon nanoparticle thin films show significant gating with distinct hysteresis in their current–voltage characteristics. Device performance strongly depends on measurement environment and charge transport is determined by particle surfaces. Particle encapsulation with polymethyl methacrylate or Al2O3 reduces hysteresis and device sensitivity against environmental influences. Both Al2O3 coating and UV exposure during measurements alter current transport and enhance conductivity, providing evidence for surface-dominated transpor
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.LEB.conduc
Keywords: silicon; nanoparticle; thin; film